Conception of 6th-Year students on Solid Wast based on activities using the “Extraordinary Waste” documentary (Research, Society and Development, 2018)
It is considered important that complex issues such as solid waste be addressed at the school. The objective was to verify the conceptions of the students of the 6th grade of a Public School (Northwest Paulista) solid waste, covering social, environmental and health issues and based on the documentary "Extraordinary Waste". For this, a didactic sequence was developed using the Dialectic Mediation Methodology (DMM), which provides for four steps: 1.Retraining, 2.Problematizing, 3. Systematizing and 4.Producing. The students elaborated texts and drawings that were analyzed and grouped according to categories. It was verified that through DMM the students were able to develop concepts on the theme solid waste, representing social and health issues, in addition to the environmental ones, traditionally worked on school curriculum. The choice of  "Extraordinary Wast" Documentary (step 2) was essential to broaden students' vision. This fact can be observed in the analysis of the students' final work (step 4), wich they pointed out subjects such as prejudice, precariousness, neglect and health, in their representations.